Fowl typhoid live lyophilized vaccine applied at 3-month intervals protected layer chickens from Salmonella gallinarum infection and prevented cloacal shedding - Akter, Taslima; Nooruzzaman, Mohammed; Belal, Sheikh Mohammad Shariful Hoque; Ahammed, Mustak; Uddin, ABM Jalal; Parvin, Rokshana; Khan, Md Abu Hadi Noor Ali; Islam, Md Ariful; Hossain, Md Mokbul (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: Here, we developed and tested the efficacy of a vaccination protocol based on a commercially available live attenuated Salmonella enterica serovar Gallinarum (Salmonella gallinarum) in layer chickens. Materials and Methods: 50 layer chickens of 16 weeks age were obtained and divided into two groups (n = 25), control and vaccinated. The vaccinated group received Salmonella vaccine at 0.2 ml/bird, s/c route at 16, 18, 30, and 42 weeks of age. At 21 weeks of age, birds from both groups were challenged with S. gallinarum orally at 4 × 107 colony-forming unit per bird. Results: Both rapid serum plate agglutination and enzyme-linked immunosorbent assay demonstrated a rising rate of seroconversion in vaccinated birds across the study period, with a 4% positive rate at 18 weeks, 56% at 21 weeks, 60% at 30 weeks, and 64% at each time point of 42 and 54 weeks. The vaccine showed 100% clinical protection and reduced the Salmonella shedding in the feces and eggs of the challenged birds. On the contrary, the unvaccinated challenged birds showed clinical signs and lesions typical of Salmonella infections with morbidity and mortality rates of 36% and 20%, respectively, and had high rates of Salmonella shedding in feces and eggs. Conclusions: With the proposed vaccination schedule Salmonella shedding was prevented, and a high seroconversion was confirmed. To prevent Salmonella infections in laying flocks, a 3-month interval immunization program is advised starting at the pre-laying stage. J. Adv. Vet. Anim. Res., 9(2): 301–309, June 2022 http://doi.org/10.5455/javar.2022.i597